Ultrasonography of the Vagus Nerve in Parkinson's Disease - Fedtke, Nadin; Witte, Otto W.; Prell, Tino (Frontiers in Neurology, 2018)
Based on the topographic distribution of α-synuclein-enriched Lewy bodies, it has been hypothesized that Parkinson´s disease may start in the gastrointestinal tract and gain access to the central nervous system via the vagus nerve. Since ultrasonography is a powerful tool to study peripheral nerve disturbances, we conducted ultrasonography of the vagus nerve in 32 patients with Parkinson´s disease, 15 disease controls and 15 healthy controls. The cross-sectional area and echogenicity measured on transverse scans of the vagal nerve did not differ significantly between these groups. Therefore, the observed intraneuronal changes in Parkinson´s disease are not associated with ultrasonographic disruptions of the vagus nerve integrity.